1995
DOI: 10.1111/j.1365-2249.1995.tb03725.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased IL-2, IL-4 and interferon-gamma (IFN-γ) in steroid-sensitive nephrotic syndrome

Abstract: SUMMARYWe investigated the production of cytokines by peripheral blood mononuclear cells (PBMC) and serum cytokine concentrations in children with steroid-sensitive idiopathic nephrotic syndrome (SSNS). PBMC from patients off treatment were collected during remission and relapse and cultured in medium alone or stimulated with calcium ionophore plus phorbol myristate acetate. Control PBMC were taken from healthy age-matched children. IL-2 was measured by bioassay, IL-4 by immunoradiometric assay, and IL-8 and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 34 publications
2
58
0
7
Order By: Relevance
“…This was in contrast to the published study by Gulati et al (4), in which patients with late steroid + expression in FSGS rituximab responders compared with those in both nonresponders and controls, and it was associated with significantly reduced mitogen-stimulated CD3 production of IFN-g and IL-2. The baseline immunologic signature in our FSGS rituximab responders was also significantly different from that in patients with MCNS in relapse as shown in Table 3, indicating that the immunologic basis underlying the nephrotic syndrome is likely to be distinct in this group of FSGS rituximab responders compared with those in patients with MCNS, in whom increased mitogen-stimulated lymphocyte production of IL-2 and IFN-g has been shown (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 78%
“…This was in contrast to the published study by Gulati et al (4), in which patients with late steroid + expression in FSGS rituximab responders compared with those in both nonresponders and controls, and it was associated with significantly reduced mitogen-stimulated CD3 production of IFN-g and IL-2. The baseline immunologic signature in our FSGS rituximab responders was also significantly different from that in patients with MCNS in relapse as shown in Table 3, indicating that the immunologic basis underlying the nephrotic syndrome is likely to be distinct in this group of FSGS rituximab responders compared with those in patients with MCNS, in whom increased mitogen-stimulated lymphocyte production of IL-2 and IFN-g has been shown (27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 78%
“…A potential candidate for a permeability factor is IL-8/CXCL8. Most studies that assessed this chemokine in INS found increased serum levels in patients during relapse, and normal concentrations in remission (7,8,38). IL-8/CXCL8 was also found to have effects on the metabolism of the glomerular basement membrane, possibly increasing glomerular permeability (7).…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli, such as allergens, may activate common immune mechanisms, which subsequently result in proteinuria in children with MCNS. Several investigators have demonstrated the potential role of Th2 cytokines in this disease [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%